Dialogic pedagogical gatherings in teaching the history of education: An online training experience - González Rodríguez, Juan Agustín; Bernad Cavero, Olga; López Teulón, María Paz (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
Dialogic Pedagogical Gatherings is a technique that has been previously used in different educational contexts. However, its implementation in virtual environments is not so common. The present paper reflects an experience of this technique applied to the telematic training of Social Education students in a subject linked to the history of education. The results obtained were compared with other similar experiences in face-to-face format, evidencing that the Dialogic Pedagogical Gatherings have had good results in the online format, although there are elements of improvement for future implementations.